Quantitative and qualitative analysis of sugarcane productivity in function of air temperature and water stress - Casaroli, Derblai; Alves Júnior, José; Pêgo Evangelista, Adão Wagner (Comunicata Scientiae, 2019)
Climate variables can influence the both productivity and quality of the commercial product of sugarcane crop. This study aimed to evaluate the influence of thermal time, negative degree-days and water deficit on productivity and industrial quality of sugarcane for the Goiás Brazilian Savanna region. The data of productivity and industrial quality were obtained in the field (Plant Centro Álcool®) and climate data in the weather station. Thermal time and the accumulation of negative degree-days in cycles showed significant correlations with the yield. The highest (340 mm) and the lowest (158 mm) accumulated water deficit blade not reflected in lower productivity and greater, respectively. Relative evapotranspiration (rET) was equal at 1.0 in more than 50% of the studied period, in which not were found significant correlations between the rET<1 with the productivity and industrial quality. We found significant correlations between rates of degree-days and negative degree-days with productivity rates; however, there was a low correlation between the water deficit rates and productivity. The total recoverable sugars rates and total soluble solids showed maximum accumulation point only in function of degree-day rates. We conclude that the thermal time has greater influence on yield decrease of sugarcane with different harvest cycles, significantly contributing to the accumulation of sugars in the stem.